Sex, drugs and escape: a psychological model of HIV-risk sexual behaviours. - McKirnan DJ; Ostrow DG; Hope B (AIDS Care)
The lack of an effective HIV vaccine or other biomedical intervention means that behavioural change will continue to be critical to the prevention of HIV infection. Despite near universal knowledge of HIV and sexual safety, and widespread intentions to be safe, rates of unprotected sex and HIV sero-conversion remain high among gay and bisexual men. Explanatory models that link risk-taking and prevention to rational processes such as knowledge, social norms, behavioural intentions, or perceived vulnerability to infection, cannot fully account for the continued risk behaviours observed in virtually all cohorts of gay men. We feel that innovative conceptions of risk and risk prevention are needed, that emphasize non-rational, affective processes in risk-taking and decision-making. Consistent with recent models from social psychology, we propose that for many people sexual risk does not stem from a lack of community norms or personal standards, but from a desire to escape cognitive awareness of very rigorous norms and standards. Being self-aware of HIV risk arouses anxiety and precludes highly-desired activities: fatigue, fatalism, or other negative affect over HIV may lead people to 'cognitively disengage' within the sexual situation, and not to follow their norms or intentions toward safety. We propose that both substance use and the approach of high stimulation or other sexual settings facilitates this cognitive disengagement, wherein people enact 'automatic' sexual scripts and/or become more responsive to external pressures toward risk. We briefly review current psychosocial models of HIV risk behaviour, outline a cognitive escape model with particular emphasis on substance use as a behavioural risk factor, and discuss implications of an escape model for behavioural interventions among gay and bisexual men.